Tax Structure in Nepal: Its Impact on the Real Economy (Pragyaratna प्रज्ञारत्न, 2024)
The objective of this paper is to study the tax structure of Nepal and its impact on the real economy. The data collected from various published data sources like Economic Survey of Nepal, Nepal Rastra Bank, World Bank, IMF and other institutions are used to test regression models to reach at conclusion of the research paper. This article reviews the structure of Nepal's tax systems and looks at how they affect economic growth, redistribution of income, and macroeconomic stability. Studies reveal that Nepal's relatively higher dependency on direct taxes restrains economic expansion, however not as much as in the "Rest of the World." Still, Nepal's greater reliance on direct taxes does not appear to materially reduce economic volatility or income inequality, unlike most other countries.